2023
DOI: 10.3390/rs15051339
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Annual Sedimentation through High Accuracy UAV-Photogrammetry Data and Comparison with RUSLE and PESERA Erosion Models

Abstract: Model-based soil erosion studies have increased in number, given the availability of geodata and the recent technological advances. However, their accuracy remains rather questionable since the scarcity of field records hinders the validation of simulated values. In this context, this study aims to present a method for measuring sediment deposition at a typical Mediterranean catchment (870 ha) in Greece through high spatial resolution field measurements acquired by an Unmanned Aerial Vehicle (UAV) survey. Thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 129 publications
(197 reference statements)
0
3
0
Order By: Relevance
“…Optimal study sites are areas of limited or no vegetation. These sites relate to post-fire settings, settings controlled by overgrazing [111][112][113][114][115][116][117][118], or areas of high sedimentation, where eroded, transported sediments constantly cover the recently formed vegetation (as at the Platana test site [47]). To our knowledge, no detailed soil erosion investigation has yet been conducted regarding the combination of UAV-and t-LiDAR-derived point cloud algorithms in fire-affected areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Optimal study sites are areas of limited or no vegetation. These sites relate to post-fire settings, settings controlled by overgrazing [111][112][113][114][115][116][117][118], or areas of high sedimentation, where eroded, transported sediments constantly cover the recently formed vegetation (as at the Platana test site [47]). To our knowledge, no detailed soil erosion investigation has yet been conducted regarding the combination of UAV-and t-LiDAR-derived point cloud algorithms in fire-affected areas.…”
Section: Discussionmentioning
confidence: 99%
“…There has been a surge of interest in the Unmanned Aerial Vehicle (UAV) Structure from Motion (SfM) data collection technique, primarily driven by the cost-effectiveness of the equipment and the enhanced speed of data acquisition. This method, combined with recent advancements in computer technology, has positioned photogrammetry as a robust tool for geomorphological research [47]. Applications across various domains, such as monitoring riverbed topography [48][49][50][51], riverbank analysis [52,53], erosion [38,[54][55][56][57], landslides [58], erosion rate assessment [59][60][61][62][63][64], coastal analysis [65], and rockfall/rock slope stability analysis [66], have significantly expanded the realm of geomorphological analysis.…”
Section: Introductionmentioning
confidence: 99%
“…UAV technology has been successfully employed in soil erosion monitoring studies, and Sebastian et al (2012) were among the pioneers in utilizing UAVs to create high-precision DTMs and orthoimages to achieve superior monitoring outcomes. Furthermore, Alexiou et al (2023) demonstrated the utility of high-resolution UAV imagery in measuring sediment deposition in a typical Mediterranean watershed. The high level of detail and spatial resolution offered by UAV imagery enable the identification and characterization of fine-scale landscape features related to soil erosion, leading to more accurate assessments of the soil erosion distribution and patterns compared to traditional methods such as satellite imagery and ground-based surveys.…”
Section: Discussionmentioning
confidence: 99%